Le Nord au Sud : 25 ans d'art en Belgique (1947-1972). (Marseille : Musée Cantini, 1972)
Alechinsky, Pierre ; Bogart, Bram ; Broodthaers, Marcel ; Burssens, Jan ; Bury, Pol ; Chemay, Jacques ; Dotremont, Christian ; Elias, Etienne ; Folon, Jean-Michel ; Gentils, Vic ; Giltaix, Daniel ; Lacomblez, Jacques ; Laenen, Jean-Paul ; Landuyt, Octave ; Mara, Pol ; Nellens, Roger ; Panamarenko ; Persoons, Hans ; Raveel, Roger ; Reinhoud ; D'Haese, Roel ; Roobjee, Pjeeroo ; Roulin, Félix ; Vandercam, Serge ; Van Hoeydonck, Paul ; Verheyen, Jef ; Wijckaert, Maurice
Le Nord au Sud : 25 ans d'art en Belgique (1947-1972), Musée Cantini, Marseille, 29 mai - 15 septembre 1972
boek
Keywords: België